2008
DOI: 10.1097/tp.0b013e31816c7dc7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Polymorphism in the IL-12p40 Gene and Cytomegalovirus Reactivation After Kidney Transplantation

Abstract: This study identified a new genetic risk factor for CMV reactivation after kidney transplantation. The results of our study suggest that C carriers might especially benefit from CMV prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Polymorphisms in innate cytokine signaling, e.g., in TLR2, in the IL-12 promoter, or in the IL-12 receptor, have been shown to affect immune responses in different infections including HCMV (40)(41)(42)(43). It is possible that these polymorphisms partially account for the remarkable donor variability in our study.…”
Section: Cd14mentioning
confidence: 78%
“…Polymorphisms in innate cytokine signaling, e.g., in TLR2, in the IL-12 promoter, or in the IL-12 receptor, have been shown to affect immune responses in different infections including HCMV (40)(41)(42)(43). It is possible that these polymorphisms partially account for the remarkable donor variability in our study.…”
Section: Cd14mentioning
confidence: 78%
“…Infection with T. gondii has been associated with genes encoding interferon gamma, tolllike receptors, and the purinergic receptor P2X 7 [41][42][43] . CMV susceptibility is attributed in part to polymorphisms in several genes including those encoding cytokines, toll-like receptors, and other immune response molecules [34,44,45] . Alterations in the HLA region and polymorphisms in genes encoding cytokines are linked to EBV susceptibility [46,47] .…”
Section: Discussionmentioning
confidence: 99%
“…35 It has been reported that IL12B 3'UTR C allele may be a risk factor for CMV reactivation in renal transplant recipients. 13 In the present study, IL12B 3'UTR AC genotype was found to postpone Chronically high viral load (CHVL) resolved by the 24th month from CHVL onset, in significantly higher proportion of patients carrying dominant homozygous IL12B 3'UTR AA genotype compared to heterozygous IL12B 3'UTR AC individuals (80.6% vs 53.5%, p = 0.034, by log-rank test). The length of the high viremia period was analyzed in CHVL patients, after primary EBV infection or reactivation occurring during the first year post-LTx, and defined as the time between the first EBV DNA level above 4000 copies/g DNA and the time of the first 2 consecutive values below this level (i.e.…”
Section: Discussionmentioning
confidence: 72%
“…20 SNPs of: IL-1␤ −511C/T (rs16944), IL-1␤ +3954C/T (rs1143634), IL12B 3'UTR A/C (rs3212227), and CCL2 −2518A/G (rs1024611), were assessed by PCR amplification and restriction fragment length polymorphism analysis, as previously reported. 13,[21][22][23] The presence of 32-base pair (bp) deletion within the CCR5 encoding gene (CCR5 32, rs333) and variable number of tandem (86-bp) repeats (VNTR) in the intron 2 of the IL-1RN gene (rs2234663) were analyzed by PCR. 24,25…”
Section: Cytokine Gene Polymorphism Analysismentioning
confidence: 99%